Olfactory Neuroblastoma: Fate of the Neck—A Long‐term Multicenter Retrospective Study. (15th December 2015) - Nalavenkata, Sunny B.; Sacks, Raymond; Adappa, Nithin D.; Palmer, James N.; Purkey, Michael T.; Feldman, Michael D.; Schlosser, Rodney J.; Snyderman, Carl H.; Wang, Eric W.; Woodworth, Bradford A.; Smee, Robert; Havas, Thomas E.; et al.
Abstract : Objective: Olfactory neuroblastoma and the management of neck disease has posed considerable challenges to the treating physician. The aims of the study were to determine the incidence and factors influencing neck disease and to identify at‐risk patients with cervical node–negative disease at presentation. Study Design: Multicenter case series with retrospective chart review. Setting and Subjects: In sum, 113 patients with a histopathologic diagnosis of olfactory neuroblastoma across 6 tertiary hospitals in Australia and the United States. Methods: Treatment modalities for the primary site and neck included surgery, radiotherapy, and combined therapy. Treatment outcomes were measured in relation to date of primary treatment, and long‐term follow‐up was recorded. Disease‐free survival was calculated as time for patients to develop delayed neck disease following primary treatment. Results: A total of 113 patients (46 females, 49.7 ± 13.2 years) were identified with a median follow‐up of 41.5 months (interquartile range, 58.2); 7.1% of patients presented with primary neck disease, while 8.8% of patients presented with delayed neck disease. Neck disease was present in patients with Hyams grade II (22.2%), III (55.6%), and IV (22.2%) lesions (χ 2 = 5.66, P =. 13). Histologic grade was higher in patients with primary neck disease (χ 2 = 16.22, P =. 001). Positive surgical margins were associated with a higher risk of delayed neck disease as compared with clear surgical margin (17.9% vs 5%, P =. 034). Conclusion: Neck metastasis is an important clinical consideration for olfactory neuroblastoma at presentation and in surveillance. Primary treatment of the neck could be considered in select patients. Long‐term surveillance of the neck and primary site is essential.